Crosstalk and Field to Wire Coupling Problems: The Spice Simulator Approach - BROYDE, Frederic; Clavelier, Evelyne; Vaillant, Frederic; Bigot, Serge (9th International Zurich Symposium and Technical Exhibition on Electromagnetic Compatibility, 1991)
A new approach is presented for the simulation of crosstalk on a bundle of n conductors, and the effect of its excitation by an external field. This approach is based on a multiconductor line model in which the line is divided longitudinally into segments, on which the amplitude and phase of the incident field are assumed constant. We establish an equivalent circuit for the line, suitable for a SPICE simulation software. This equivalent circuit includes n-1 two-conductors transmission lines, each of them provided with two field equivalent sources, the amplitude of which is determined by an other equivalent circuit. The determination of the parameters (i.e. the component values) of the equivalent circuits is obtained with a dedicated software, but the simulation itself is done by a conventional SPICE simulator. We demonstrate practical examples of calculation and their comparison with experiment is shown and discussed.